Найдите производную функции: f(x)=x^2(x-5) x0=-4 f(x)=3x-4x^3 x0=5 f(x)=x^7-3x^6+3x^3-23 x0=-1 f(x)=x^2(x-5) x0=-4

Найдите производную функции: f(x)=x^2(x-5) x0=-4 f(x)=3x-4x^3 x0=5 f(x)=x^7-3x^6+3x^3-23 x0=-1 f(x)=x^2(x-5) x0=-4
Гость
Ответ(ы) на вопрос:
Гость
f(x)=x²(x-5); x0=-4 f'(x)=2x(x-5)+x²=-8*(-9)+16=88 f(x)=3x-4x³ ;x0=5 f'(x)=3-12x²=3-12*25=-297 f(x)=x⁷-3x⁶+3x³-23 x0=-1 f'(x)=7x⁶-18x⁵+9x²=7+18+9=34
Гость
[latex]f(x)=x^2(x-5);x_0=-4 \\ f'(x)=2x(x-5)+x^2=2x^2-10x+x^2=3x^2-10x \\ f'(-4)=48+40=88 \\ f(x)=3x-4x^3 \\ f'(x)=3-12x^2 \\ x_0=5 \\ f'(5)=3-300=-297 \\ f(x)=x^7-3x^6+3x^3-23 \\ x_0=-1 \\ f'(x)=7x^6-18x^5+9x^2 \\ f'(-1)=7+18+9=34[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы